-56=7+7x

Simple and best practice solution for -56=7+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -56=7+7x equation:


Simplifying
-56 = 7 + 7x

Solving
-56 = 7 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-56 + -7x = 7 + 7x + -7x

Combine like terms: 7x + -7x = 0
-56 + -7x = 7 + 0
-56 + -7x = 7

Add '56' to each side of the equation.
-56 + 56 + -7x = 7 + 56

Combine like terms: -56 + 56 = 0
0 + -7x = 7 + 56
-7x = 7 + 56

Combine like terms: 7 + 56 = 63
-7x = 63

Divide each side by '-7'.
x = -9

Simplifying
x = -9

See similar equations:

| 9-3x=7x+19 | | 8(x+7)-(5x-9)=1 | | .37+1.1m=2.65m-1.18 | | 4x+18=34 | | 11x+5x-1=32 | | -5x-7=41-x | | 2.4=16x | | 12(1.15)= | | y*6=3.3 | | 4x^2+20x+12=x+20 | | x+6=-7x+86 | | 1/2(x+4)=1/3(3x-6) | | -3(-2x+7)=-81 | | x+31=78 | | 3-3.7(8-x)=16.5 | | 19=2a-(a+1) | | 7x-56=9-3x+5-4x | | n-40=47 | | 4y=28 | | -11-5=(5x+4) | | z-9=4 | | x^4+2x^3+1=0 | | 23=m+36 | | 8y+5=7y-5 | | .25d= | | 5(3x+9)=37 | | 1.5x+.2x=1.833x-0.1333 | | 8(x-2)=-40 | | 6x^2-30x+36=12 | | 180=x+64+x+134 | | 6(x/2-4)=21+6x | | 3n+7-n=23 |

Equations solver categories